2017
DOI: 10.1186/s12866-017-1116-1
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent interactions of Streptococcus gallolyticus subsp. gallolyticus with human blood cells

Abstract: Background Streptococcus gallolyticus subsp. gallolyticus (S. gallolyticus) is the causative pathogen in up to 20% of streptococcal-induced infective endocarditis (IE) cases. However, the underlying mechanisms of pathogenesis in S. gallolyticus have not yet been solved. Pathogens causing IE need to employ virulent strategies to initiate and establish infections, such as escape the bloodstream, invade the host-cell, and persist intracellularly. In this study, we examined the induction of inflammation by differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Many isolates induced aggregation in one or two donors but not all three, suggesting that aggregation is not only a matter of bacterial properties, but also dependent on host factors. This is consistent with previous findings about aggregation induced by Sg gallolyticus ( 28 ). To determine which host factors are of importance, a larger study with more donors would be required.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Many isolates induced aggregation in one or two donors but not all three, suggesting that aggregation is not only a matter of bacterial properties, but also dependent on host factors. This is consistent with previous findings about aggregation induced by Sg gallolyticus ( 28 ). To determine which host factors are of importance, a larger study with more donors would be required.…”
Section: Discussionsupporting
confidence: 94%
“…For SBSEC, there is limited research regarding the interactions with platelets. Veloso et al ( 27 ) showed that a strain of Sg gallolyticus induced platelet aggregation, and a study by Grimm et al ( 28 ) suggested that aggregation is both host and isolate dependent. However, no studies have investigated which host and bacterial factors are important for this interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also confirmed that both high- and low-virulence strains can adhere to the intestinal mucosa, ensuring that adhesion to enterocytes and intracellular cell proliferation are key factors in the pathogenesis of SG ( Kimpe et al, 2003 ; Abranches et al, 2011 ; Kumar et al, 2022 ). Interestingly, the induction of inflammation by different SG strains was associated with their intracellular survivability in red blood cells and macrophages ( Grimm et al, 2017 ). To better understand this potential mechanism, it is important to consider the general pathogenesis of Streptococcus infections and the specifics of SG infection in turkeys, as demonstrated in humans previously.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, S. gallolyticus possesses a unique virulence factor that promotes infection in susceptible individuals and depends on pre-existing colonic abnormalities [13]. The unique pathogenicity of S. gallolyticus isolates was determined by the difference of individual virulence factors during the interaction between dependent differences and human blood cells, which constitute further elucidating the mechanisms in the complex pathogenesis of the IE pathogen [14]. However, the understanding of antibiotic resistance and virulence factors is limited and the pathogenesis of infection remains elusive.…”
Section: Introductionmentioning
confidence: 99%